Implications of Unconnected Micro, Molecular, and Molar Level Research in Psychology: The Case of Executive Functions, Self-Regulation, and External Regulation - de la Fuente, Jesús; González-Torres, María Carmen; Aznárez-Sanado, Maite; Martínez-Vicente, José Manuel; Peralta-Sánchez, Francisco Javier; Vera, Manuel Mariano (Frontiers in Psychology, 2019)
The proliferation of research production in Psychology as a science has been increasing exponentially. This situation leads to the necessity of organizing the research production into different levels of analysis that make it possible to delimit each research domain. The objective of this analysis is to clearly distinguish the different levels of research: micro-analysis, molecular and molar. Each level is presented, along with an analysis of its goodnesses and limitations. Next, this analysis is applied to the topics of Executive Functions, Self-Regulation and External Regulation. Conclusions, limitations and implications for future research are offered, with a view toward better connection of research production across the different levels, and an allusion to ethical considerations.